Pengaruh Pembiayaan UMKM, CAR, dan NPF Terhadap Return on Assets Bank Umum Syariah di Indonesia - Hani Nuraeni; Fifi Afiyanti Tripuspitorini; Rosma Pakpahan (Journal of Applied Islamic Economics and Finance, 2022)
MSME financing and CAR are expected to increase the profit of Islamic banks. NPF is a factor that is thought to reduce profits. This study was to determine the effect of MSME financing in the working capital and investment categories, the effect of CAR, and the effect of NPF for Islamic Commercial Banks in Indonesia on ROA. This study uses a descriptive-quantitative method that analyzes secondary data, namely the monthly financial ratios, with multiple linear regression data analysis methods. The results showed that partially the MSME financing variable in the working capital and investment categories did not have a significant effect on ROA, while CAR had a positive and significant effect on ROA, and NPF had no significant effect on ROA. Simultaneously, the variables PUMKM, CAR, and NPF have a positive and significant effect on ROA. The variables PUMKM, CAR, and NPF have a contribution to explaining the profitability of 85.55%.